2014
DOI: 10.2807/1560-7917.es2014.19.3.20681
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous dengue virus infection in Japan imported into Germany, September 2013

Abstract: In September 2013, dengue virus (DENV) infection was diagnosed in a German traveller returning from Japan. DENV-specific IgM and IgG and DENV NS1 antigen were detected in the patient's blood, as were DENV serotype 2-specific antibodies. Public health authorities should be aware that autochthonous transmission of this emerging virus may occur in Japan. Our findings also highlight the importance of taking a full travel history, even from travellers not returning from tropical countries, to assess potential infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…Autochthonous infection recently occurred in the states of Florida and Texas in the USA, France, and Croatia (5-7). A German traveler was suspected to be infected with DENV in Yamanashi prefecture next to Tokyo in 2013 (8). Autochthonous cases were finally confirmed in Japan in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Autochthonous infection recently occurred in the states of Florida and Texas in the USA, France, and Croatia (5-7). A German traveler was suspected to be infected with DENV in Yamanashi prefecture next to Tokyo in 2013 (8). Autochthonous cases were finally confirmed in Japan in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…DENV enfeksiyonu, Orta-Güney Amerika ve Güneydoğu Asya ile DENV'nin yeni belirlendiği Afrika ile Karayip ve Pasifi k adaları gibi dünyanın birçok tropikal bölgesinde endemiktir 14 . Son yıllarda kıtalar arası yoğun seyahat nedeniyle endemik bölgeleri ziyaret eden birçok duyarlı bireyin hastalıkla temas ettiği ve virusun Avrupa ülkelerine kadar taşındığı bildirilmektedir 15 .…”
Section: Introductionunclassified
“…A. albopictus is present in Japan, and in August 2012, invasion of the yellow fever mosquito, A. aegypti, was reported at Narita International Airport (3) and then at Haneda International Airport in early to mid-2013 (personal communication). Moreover, in late August 2013, a single DENV infection was confirmed in a German individual travelling to Japan (4,5). In this study, we demonstrated the susceptibility of foreign (imported) and Japanese (indigenous) Aedes mosquito spp.…”
mentioning
confidence: 51%